Visual images of the biological microcosmos: Viewers’ perception of realism, preference, and desire to explore - Höst, Gunnar; Schönborn, Konrad J.; Tibell, Lena (Frontiers in Education, 2022)
Visual images are crucial for communicating science in educational contexts and amongst practitioners. Reading images contributes to meaning-making in society at large, and images are fundamental communicative tools in public spaces such as science centers. Here, visitors are exposed to a range of static, dynamic, and digital visual representations accessible through various multimodal and interactive possibilities. Images conveying scientific phenomena differ to what extent they represent real objects, and include photographs, schematic illustrations, and measurement-based models. Depicting realism in biological objects, structures and processes through images differs with respect to, inter alia, shading, color, and surface texture. Although research has shown that aspects of these properties can both potentially benefit and impair interpretation, little is known about their impact on viewers’ visual preference and inclination for further exploration. Therefore, the aim of this study is to investigate what effect visual properties have on visitors’ perception of biological images integrated in an interactive science center exhibit. Visitors responded to a questionnaire designed to assess the impact of three indicators of realism (shading, color, and surface texture) and biological content (e.g., cells and viruses) on participants’ preferences, perceptions of whether biological images depicted real objects, and their desire to further explore images. Inspired by discrete choice experiments, image pairs were systematically varied to allow participants to make direct choices between images with different properties. Binary logistic regression analysis revealed that the three indicators of realism were all significant predictors of participants’ assessments that images depict real objects. Shadows emerged as a significant predictor of preference for further exploration together with the presence of cells in the image. Correlation analysis indicated that images that were more often selected as depicting real objects were also more often selected for further exploration. We interpret the results in terms of construal level theory in that a biological image perceived as a realistic portrayal would induce a desire for further exploration. The findings have implications for considering the role of realism and preference in the design of images for communicating science in public spaces.